ANALISIS KUALITAS LAYANAN ATM DAN KEPUASANPENGGUNA TERHADAP LOYALITAS PELANGGAN DENGANPENDEKATAN STRUCTURAL EQUATION MODELLING (UI Scholars Hub, 2015)
This research has been prepared for the purpose of reviewing the impact of the quality of services provided by ATM on one of the largest private bank in Indonesia on customer loyalty. In this case the quality of the service will be tested at one of the ATM Bank the largest private bank in Indonesia which consists of quality information and quality on customer loyalty ATM system on one of the largest private bank in Indonesia which is mediated by customer satisfaction. T-count value obtained from Confirmatory Factor Analysis (CFA) for all variables showed that all the questions are included in all variables statistically significant. The coefficient of Goodness of Fit meets the requirements of the suitability of a model, it can be concluded that in general, the model obtained has a good level of compatibility. ATM service quality has a statistically significant positive relationship with customer loyalty. Satisfaction with the quality of the information content of ATM and satisfaction with the performance of the ATM system did in fact have a positive relationship with customer satisfaction. Variable satisfaction statistically significant influenced by two independent variables, namely variable quality and Quality Information System. Satisfaction will impact on the confidence of customers to use ATMs that will appear on the ATM customer loyalty to the Bank. In accordance with the hypothesis that the satisfaction variables provide a statistically significant effect on the variable loyalty.